Novel Hybrid Metaheuristics And Algorithm Extensions For Optimization Of Engineering Applications - Chiao Mei, Florence Choong (2010)
NP-hard optimization problems that are found in many engineering domains pose great challenges to traditional algorithmic solutions. The search space normally encompasses a huge number of local optimal and the computational effort to achieve a global optimum can be very huge for practical use. In this thesis, the design, analysis. improvement and application of metaheuristics for hard CO problems is presented. The research is motivated by four engineering applications that covers high-level synthesis, multiprocessor scheduling, flexible manufacturing systems and hybrid flow shop scheduling.